New Insights into Hepatic and Intestinal Microcirculation and Pulmonary Inflammation in a Model of Septic Shock and Venovenous Extracorporeal Membrane Oxygenation in the Rat - Edinger, Fabian; Zajonz, Thomas; Holtz, Lena; Schmidt, Götz; Schneck, Emmanuel; Sander, Michael; Koch, Christian; Justus Liebig University Giessen (My University, 2024)
Treatment of critically ill patients with venovenous (V-V) extracorporeal membrane oxygenation (ECMO) has gained wide acceptance in the last few decades. However, the use of V-V ECMO in septic shock remains controversial. The effect of ECMO-induced inflammation on the microcirculation of the intestine, liver, and critically damaged lungs is unknown. Therefore, the aim of this study was to measure the hepatic and intestinal microcirculation and pulmonary inflammatory response in a model of V-V ECMO and septic shock in the rat. Twenty male Lewis rats were randomly assigned to receive V-V ECMO therapy or a sham procedure. Hemodynamic data were measured by a pressure-volume catheter in the left ventricle and a catheter in the lateral tail artery. Septic shock was induced by the intravenous infusion of lipopolysaccharide (1 mg/kg). During V-V ECMO therapy, rats received lung-protective ventilation. The hepatic and intestinal microcirculation was assessed by micro-lightguide spectrophotometry after median laparotomy for 2 h. Systemic and pulmonary inflammation was measured by enzyme-linked immunosorbent assays of plasma and bronchoalveolar lavage (BAL), respectively, which included tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), IL-10, C-X-C motif ligand 2 (CXCL2), and CXCL5. Reduced oxygen saturation and relative hemoglobin concentration were measured in the hepatic and intestinal microcirculation during treatment with V-V ECMO. These animals also showed increased systolic, mean, and diastolic blood pressures. While no differences in left ventricular ejection fraction were observed, animals in the V-V ECMO group presented an increased heart rate, stroke volume, and cardiac output. Blood gas analysis showed dilutional anemia during V-V ECMO, whereas plasma analysis revealed a decreased concentration of IL-10 during V-V ECMO therapy, and BAL measurements showed increased concentrations of TNF-α, CXCL2, and CXCL5. Rats treated with V-V ECMO showed impaired microcirculation of the intestine and liver during septic shock despite increased blood pressure and cardiac output. Despite lung-protective ventilation, increased pulmonary inflammation was recognized during V-V ECMO therapy in septic shock.
Keywords: ddc:610